1997
DOI: 10.2165/00003088-199733040-00001
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Pharmacokinetics of Irinotecan

Abstract: This article reviews the clinical pharmacokinetics of a water-soluble analogue of camptothecin, irinotecan [CPT-11 or 7-ethyl-10-[4-(1-piperidino)-1-piperidino]-carbonyloxy-camptoth eci n]. Irinotecan, and its more potent metabolite SN-38 (7- ethyl-10-hydroxy-camptothecin), interfere with mammalian DNA topoisomerase I and cancer cell death appears to result from DNA strand breaks caused by the formation of cleavable complexes. The main clinical adverse effects of irinotecan therapy are neutropenia and diarrhoe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
149
0
9

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(169 citation statements)
references
References 69 publications
7
149
0
9
Order By: Relevance
“…Intratumoral SN-38 was only measurable at concentrations 50 times lower than CPT-11. It is known that only a limited amount of CPT-11 is transformed into SN-38 (Chabot, 1997), which agrees with plasma levels being about 12 times lower than CPT-11 in our study (data not shown). Intratumoral SN-38 levels were somewhat higher after anti-VEGF therapy, but not significantly.…”
Section: Anti-vegf Mab Does Not Impair Intratumoral Cpt-11 Deliverysupporting
confidence: 92%
“…Intratumoral SN-38 was only measurable at concentrations 50 times lower than CPT-11. It is known that only a limited amount of CPT-11 is transformed into SN-38 (Chabot, 1997), which agrees with plasma levels being about 12 times lower than CPT-11 in our study (data not shown). Intratumoral SN-38 levels were somewhat higher after anti-VEGF therapy, but not significantly.…”
Section: Anti-vegf Mab Does Not Impair Intratumoral Cpt-11 Deliverysupporting
confidence: 92%
“…The liposomal payload, irinotecan, is a member of the camptothecin class of topoisomerase I (TOP1) inhibitors and causes cell death through DNA damage after replication-fork collisions with transiently trapped drug-TOP1-DNA cleavage complexes, thus highlighting length of drug exposure as an important driver for cytotoxicity (13). Compared with pharmacokinetic data of nonliposomal irinotecan (14), nal-IRI is characterized by a higher exposure, lower clearance, and smaller volume of distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Irinotecan serves as the water-soluble precursor of the lipophilic metabolite SN-38, which is formed by carboxylesterase-mediated cleavage of the carbamate bond between the camptothecin moiety and the dipiperdino side chain (4). SN-38 is glucuronidated to the non-toxic SN-38 glucuronide (SN-38G) in the liver via the uridine-diphospho-glucuronosyl transferase (UGT1A) enzyme family, which then releases SN-38G into the intestine for elimination (4).…”
Section: Introductionmentioning
confidence: 99%
“…SN-38 is glucuronidated to the non-toxic SN-38 glucuronide (SN-38G) in the liver via the uridine-diphospho-glucuronosyl transferase (UGT1A) enzyme family, which then releases SN-38G into the intestine for elimination (4). However, in the intestinal lumen, bacterial -glucuronidases regenerate SN-38 from SN-38G (5).…”
Section: Introductionmentioning
confidence: 99%